Pendampingan Desain Logo dan Kemasan untuk Meningkatkan Daya Saing Produk Lokal - Dicky Wisnu Usdek Riyanto (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
This service aims to increase the competitiveness of small and medium enterprises (SMEs) by developing effective logo and packaging designs. Logo and packaging design play an important role in building brand identity, attracting consumer attention, and differentiating products from competitors in a competitive market. However, many SMEs face challenges in managing and developing designs that suit the characteristics and values of their products. This service approach involves several strategic methods, including analysis of the needs and challenges of SMEs, workshops and training for education about design, direct assistance in design development, as well as ongoing monitoring and evaluation of design implementation. Through this approach, SMEs can increase their understanding of the importance of logo and packaging design, overcome implementation barriers, and increase their products' competitiveness in local and global markets. The service results showed a significant increase in the quality of logo and packaging design, positive responses from consumers, and an increase in SME brand recognition. The conclusion of this service highlights the importance of a holistic and sustainable approach in developing logo and packaging design as an integral part of SME marketing strategy. It is hoped that the experience from this service can provide inspiration and guidance for other SMEs to utilize logo and packaging design as a strategic tool in increasing the competitiveness and sustainability of their business.